Eficacia de las medidas alternativas a la prisión en Ecuador: análisis jurídico del artículo 630 del COIP - Suarez Macias, Geovanny Joel (2025)
Analyzing the effectiveness of alternative measures to imprisonment in Ecuador, using a critical-legal approach to Article 630 of the Comprehensive Organic Criminal Code (COIP), has allowed for a comprehensive assessment of their impact on criminal recidivism, social reintegration, and the perception of public safety. This study focused on examining how conditional suspension of sentences affects both the penal system and society, highlighting its limitations and proposing well-founded reforms. From a historical perspective, the Ecuadorian penal system has faced several problems, including prison overcrowding, the high economic cost of the penitentiary system, and ineffective rehabilitation of offenders. Article 630 of the COIP proposes an alternative to prison sanctions through conditional suspension of sentences for crimes with a sentence of no more than five years and that meet certain specific requirements. Among these are the offender's lack of pending proceedings, their personal history and the severity of the crime do not require the execution of a sentence, and the crimes are not serious, such as those related to gender-based violence or sexual offenses. However, our critical analysis questions the effectiveness of these measures, highlighting that, by allowing offenders to avoid prison sentences, they can be perceived as a form of impunity, negatively affecting the perception of justice and public safety. The data analyzed suggests that alternative measures do not always contribute to reducing criminal recidivism, particularly due to the lack of mandatory participation in rehabilitation programs and inadequate supervision of the conditions imposed during the suspension period. This reinforces the idea that, in their current form, these measures do not guarantee an effective transformation in offenders' behavior. The implementation of Article 630 faces significant challenges. Among the main obstacles are the absence of a solid supervisory structure, the lack of resources to monitor offenders, and the subjectivity of the assessment of criminal record and the seriousness of the offense. These deficiencies have led to inconsistent application of conditional suspension, which generates inequalities and jeopardizes the coherence of the criminal justice system. Additionally, social reintegration programs, although necessary, have limitations in terms of their scope and enforceability. Offenders under alternative measures are not always required to participate in educational, job training, or psychological support programs, which limits rehabilitation opportunities. This translates into a higher likelihood of recidivism and a system that does not fully fulfill its purpose of productively reintegrating offenders into society. Compared to international regulations, such as the United Nations Tokyo Rules and best practices from neighboring countries, the Ecuadorian legal framework, although sound in theory, lacks clear and uniform criteria for the application of alternative measures. This demonstrates the need for reforms that ensure more effective and equitable implementation. Based on these findings, several key recommendations have been put forward for reforming Article 630 of the COIP. These include restricting the application of conditional suspension to nonviolent offenses, strengthening the supervision of offenders by creating a specialized body, and establishing mandatory participation in rehabilitation programs as a prerequisite for accessing these measures. Furthermore, it is proposed to toughen penalties for noncompliance with the imposed conditions, increase investment in human and financial resources, and develop a continuous monitoring and evaluation system to measure the effectiveness of alternative measures. In conclusion, although alternative measures to prison present potential advantages, such as reducing prison overcrowding, their effectiveness in the Ecuadorian context is limited due to structural, legal, and institutional deficiencies. This critical legal analysis reinforces the need to review and reform Article 630 of the Criminal Code (COIP) to ensure that alternative measures fulfill their purpose of rehabilitating offenders, protecting public safety, and restoring confidence in the criminal justice system. The implementation of these reforms is essential to achieving a more just and efficient criminal justice system aligned with the principles of humane and equitable justice.